2017
DOI: 10.1007/s11065-017-9356-2
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Markers of Post-Stroke Depression and Apathy: a Systematic Review and Meta-Analysis

Abstract: Several brain imaging markers have been studied in the development of post-stroke depression (PSD) and post-stroke apathy (PSA), but inconsistent associations have been reported. This systematic review and meta-analysis aims to provide a comprehensive and up-to-date evaluation of imaging markers associated with PSD and PSA. Databases (Medline, Embase, PsycINFO, CINAHL, and Cochrane Database of Systematic Reviews) were searched from inception to July 21, 2016. Observational studies describing imaging markers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 145 publications
3
70
1
3
Order By: Relevance
“…We did not find any correlation between the location of hemorrhage on neuroimaging studies and depressive symptoms (p: 0.55). These findings are in agreement with previous reports [5,7,26]. However, some studies have found a significant association between PSD and left- hemisphere lesions [27].…”
Section: Discussionsupporting
confidence: 93%
“…We did not find any correlation between the location of hemorrhage on neuroimaging studies and depressive symptoms (p: 0.55). These findings are in agreement with previous reports [5,7,26]. However, some studies have found a significant association between PSD and left- hemisphere lesions [27].…”
Section: Discussionsupporting
confidence: 93%
“…Results may have been different if based, for example, on functional testing and examination by a psychologist like in other studies. It must be also kept in mind that further subjective and objective factors such as type and location of stroke play a role in the development of depressive symptoms after stroke (24). The prevalence of depression found in the present study was relatively low but still in a range that was reported in a previous systematic review (2).…”
Section: Discussionsupporting
confidence: 43%
“…In this study, we did not evaluate these factors. According to a meta-analysis, poststroke depression in the acute stroke phase is significantly associated with frontal and basal ganglia lesions, and poststroke apathy is related to hemorrhagic stroke 38 . In this study, we only included patients with first-ever acute stroke diagnosed with lacunar infarction.…”
Section: Discussionmentioning
confidence: 99%